The borderline: exploring the structural landscape of triptycene in cocrystallization with ferrocene. Issue 8 (11th February 2020) - Singh, Ajeet; Torubaev, Yury; Ansari, Shagufi N.; Singh, Sandip K.; Mobin, Shaikh M.; Mathur, Pradeep
Abstract : When the effective packing of triptycene (TripH)–ferrocene chain oligomers in their cocrystal could not be achieved, we reached a borderline at the structural landscape of TripH, where the packing of TripH molecules reproduces the pattern in the native TripH crystal. Abstract : Cocrystallization of the geometrically demanding triptycene (TripH) with the compact and electron-rich ferrocene (FcH) and its derivatives afforded C–H—πCp assembled supramolecular chains of alternating (C5 H5 )(C5 H4 R)Fe and TripH molecules in a series of binary crystals: FcH/TripH (1 ), (C10 H9 )FeCHO/TripH (2 ), diferrocenyldiacetylene/TripH (3 ), paracyclophane-C}C–Fc/TripH (4 ), and (C10 H9 )2 Fe2 /TripH (5 ). Analysis of the structure of cocrystals 1–5 (single crystal XRD) showed significant Hbridgehead —πCp interaction along with C–H—π and π—π interactions. Upon varying the groups on FcH, the appreciable Hbridgehead —πCp interaction remains in action to maintain the efficient packing and dense arrangement in the form of properly crystallized chains among the TripH and FcH derivatives mostly. In the case of 5, the effective close packing of such chain oligomers could not be achieved, so at this point, we reached a borderline at the structural landscape of TripH. This borderline can be described as an intermediate area between the native TripH and co-crystals domains, where TripH and Fc2 molecules form 2D ribbons, which are packed closely by T-shaped C–H—πPh interactions between TripH molecules which exactly reproduce the geometry of TripH—TripH interaction in the TripH native crystal.